2016
DOI: 10.1016/j.procbio.2016.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Condensed tannins from Ficus altissima leaves: Structural, antioxidant, and antityrosinase properties

Abstract: The total phenolic content and the concentration of extractable and bound condensed tannins of Ficus altissima leaves were determined. The antioxidant activity of crude extracts and condensed tannins of F. altissima leaves was evaluated using 2,2-diphenyl-1-pichydrazyl (DPPH), 2,2-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), and ferric-reducing antioxidant power (FRAP) methods. The results showed that condensed tannins possessed higher free radical scavenging power. The structure of condensed tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…The relevant biological activity of tannins is due to the interaction of these compounds with a variety of molecules, especially proteins (Barrett et al, 2017;Sekowski et al, 2017). This, added to the antioxidant properties of tannins (Karas et al, 2017;Deng et al, 2016) and anti-inflammatory (Spinaci et al, 2018;Souza et al, 2007) explain, at least in part, the pharmacological actions of these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The relevant biological activity of tannins is due to the interaction of these compounds with a variety of molecules, especially proteins (Barrett et al, 2017;Sekowski et al, 2017). This, added to the antioxidant properties of tannins (Karas et al, 2017;Deng et al, 2016) and anti-inflammatory (Spinaci et al, 2018;Souza et al, 2007) explain, at least in part, the pharmacological actions of these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, biflavonoids not containing a 1,3-benzenediol from Solanum nigrum (Figure 11) were only poor tyrosinase inhibitos, with IC 50 values > 190 µM [94]. Increasing attention has been devoted to condensed tannins, which have shown promising activities as inhibitors of both monophenolase and diphenolase activity of mushroom tyrosinase (Table 1) [96][97][98][99][100][101][102][103][104][105][106][107]. Particularly active were prodelphinidins and procyanidins from the fruit pericarp of Clausena lansium Skeels [102], as well as the complex mixtures isolated from Persea Americana [106], Longan bark [99], and from leaves and fruit of Leucaena leucocephala [97].…”
Section: Natural Phenolic Inhibitors Of Mushroom Tyrosinasementioning
confidence: 99%
“…Several studies have shown that the procyanidins from many plant sources, including Chinese hawthorn (Chai et al, 2014), indigenous cinnamon (Lin et al, 2016) and Ficus altissima leaves (Deng et al, 2016), were tested by antioxidant activities assays.…”
Section: Antioxidant Activities Of Ampsmentioning
confidence: 99%